2020
DOI: 10.1177/0013124520915571
|View full text |Cite
|
Sign up to set email alerts
|

Black and White Female Disproportional Discipline K–12

Abstract: The school-to-prison pipeline represents an educational environment that allows public schools to push many at-risk children out of school and into the juvenile justice or the adult criminal justice system. Consequently, this study explores the disproportionate rates of discipline when comparing Black and White female students in the national public-school system. Specifically, this research explored discipline outcomes for Black and White female students in kindergarten through 12th grade in five of the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The school discipline literature has evolved significantly within the last decade. Whereas early work appeared to adopt a singular approach to examining inequities in school discipline, recent studies have recognized the importance of using an intersectional lens, considering the joint effects of race and gender to understanding the disparate impact of exclusionary discipline for all students, but particularly Black girls (Blake et al, 2011; Hassan & Carter, 2021). As the field continues to mature, scholars are moving from merely documenting the presence of racial/ethnic disparities in school discipline to identifying mechanisms underlying inequitable discipline practices with the intention of formulating culturally responsive interventions and policies to curtail disparate discipline.…”
Section: Discussionmentioning
confidence: 99%
“…The school discipline literature has evolved significantly within the last decade. Whereas early work appeared to adopt a singular approach to examining inequities in school discipline, recent studies have recognized the importance of using an intersectional lens, considering the joint effects of race and gender to understanding the disparate impact of exclusionary discipline for all students, but particularly Black girls (Blake et al, 2011; Hassan & Carter, 2021). As the field continues to mature, scholars are moving from merely documenting the presence of racial/ethnic disparities in school discipline to identifying mechanisms underlying inequitable discipline practices with the intention of formulating culturally responsive interventions and policies to curtail disparate discipline.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to White children, Black children are viewed by adults as older and less innocent by age 10 (Goff et al, 2014). In school, Black students are more likely to be perceived as troublemakers and receive harsher and more frequent disciplinary actions (e.g., out of school suspension, school-related arrests) (Hassan & Carter, 2021). Within the community, approximately 21% of Black youth report having at least two interactions with the police compared to 9% of White youth, and Black youth experience negative interactions at an earlier age (Geller, 2021).…”
Section: Black Youth: Experiences Of Discrimination Today and The Rol...mentioning
confidence: 99%
“…Racial disparity in discipline is also not a regional phenomenon. In a review of national data, Hassan and Carter (2020) found that Black female students were disproportionately suspended compared with White female students in both the high and low academically performing states. The social censure and formal negative consequences of anger are more significant for children than for adults, for women than for men, for minorities than for majority people, and for employees than for employers.…”
Section: Conceptions Of Anger In Classrooms and Schoolsmentioning
confidence: 99%